Visual inspection of skiing course and terrain using virtual and augmented environment - Aleshin, V.; Klimenko, S.; Klimenko, A.; Khlamov, M.; Chuvilin, K.; Gavrilov, V. (Science and Skiing VII, 2018)
The method of the visual inspection of a skiing course and terrain designed by the authors is already working well in practice. The application developed in this project appears to be useful both for professional skiers and beginners. The rapid progress of the mobile technologies will soon allow the use of 3D models of the highest quality. It is also needed to conduct experiments on the estimation of the immersion into the virtual model and to identify the links between the degree of the immersion and the time of the run on the real slope.